Pentingnya Pembelajaran Bahasa Inggris Sebagai Muatan Lokal Untuk Siswa Sekolah Dasar Di Kabupaten Kampar: Indonesia - ZALISMAN; Yundri Akhyar; Parlindungan Simbolon; Anggi Fitri; Ayu Purnamasari S (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
English in elementary schools has long been needed until the 2013 curriculum was implemented, even though there are so many problems that are applied in implementing English learning in the classroom. Why is English in primary schools needed in learning English: first in early childhood, language learning is easier to grasp; secondly, nowadays digital age where all living systems by using English, English in elementary schools it is easier to accept the technology used. Third, by giving English to elementary schools automatically when children continue to the secondary level students will easily to mastering English. In this paper, analyzing the existence and implementation of English as local content in Kampar District based on the results of a survey of several teachers and policy makers on local content. Among them discussed whether English is appropriate or not appropriate in elementary schools in Kampar district. Several arguments and theories are presented to support both arguments. This paper believes that English can be taught in Elementary Schools (SD) or Madrasah Ibtidayah (MI) in Kampar District. Several theoretical and practical requirements can be fulfilled.